From actions to paths to patterning: Toward a dynamic theory of patterning in routines - GOH, Kenneth T. (Institutional Knowledge at Singapore Management University, 2019)
This paper demonstrates a new way of seeing and theorizing about the dynamics of organizational routines through the concept of paths – time-ordered sequences of actions or events in performing work. Empirically and conceptually, paths provide the missing link between specific actions and patterns of action. When routines are represented as a narrative network, tracing the formation and dissolution of action paths can generate new insights about the dynamic patterning of actions in routine performances. We traced action paths using longitudinal field data from a videogame development project and found that action patterns change dramatically over time based on the needs of the project. We explain these changes in terms of generic mechanisms that lead to the enactment of more (or fewer) paths in the narrative network. We propose that patterning can be seen as a new motor of routine dynamics and discuss generic mechanisms through which patterning can influence narrative network structure.